Struggling for Legitimacy: Spirit-Writing and Redemptive Societies in Republican China - Schumann, Matthias (Asian Studies E-Books Online, Collection 2026, 2026)
The Republican period was a time of radical change in which existing knowledge was questioned in light of newly introduced ideas. It seems puzzling that it was exactly during this period that the Chinese practice of spirit-writing, which had a history of more than a thousand years, experienced a boost in popularity. This book sets out to explain this puzzle. Focusing on the study of two newly founded redemptive societies, the Wushanshe and the Daoyuan, it shows how spirit-writing practitioners legitimized the practice by combining it with ideas and activities drawn from the fields of religion, Confucianism, and philanthropy. These legitimation strategies not only enabled spirit-writing practitioners to gain political acceptance, but also turned them into important actors in the social, cultural, and intellectual history of modern China